ANALISIS AGROINDUSTRI NENAS UD BERKAT BERSAMA DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Mufti Mufti; Rini Nizar; Niken Nurwati (Universitas Lancang Kuning, 2017)
Pineapple (Ananas comosus L) is a fruit crop coming from Brazil. Besides pineapple can be eaten directly can be further processed into chips pineapple, pineapple dodol, jam, syrup and others. In the village there Nenas Kualu agro-industrial raw material, namely pineapple pineapple chips, diamonds pineapple and pineapple dodol. Pineapple chips are most widely refined products developed by craftsmen in the village Kualu pineapple processing pineapple. Processing of agricultural or agro-industry is a subsystem of agribusiness very big role in increasing the added value of agricultural products. Employers will also seek to do business with a decent order to obtain the maximum revenue to improve their welfare. In connection with this condition, this study aims to conduct feasibility analysis, Break Even Point (BEP), and the added value that can be produced by the pineapple industry. The results showed that the Agro-Industry Pineapple